2011
DOI: 10.1590/s0036-46652011000500005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Taraxerol in combination with extract of Euphorbia tirucalli plant on biological parameters of Lymnaea acuminata

Abstract: SUMMARYThe present work was carried out to evaluate the molluscicidal activity of active ingredient Taraxerol with the acetone extract of Euphorbia tirucalli against Lymnaea acuminata snail. The (fecundity, hatchability and survivability) of snail L. acuminata exposed to this extract was studied. The effects of the tested extracts on life-history traits of harmful snail L. acuminata have also been evaluated, and this study also expounds the inhibitory effects of these extracts singly as well as in binary combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
3
5
0
Order By: Relevance
“…An analysis of the molluscicidal activities of the six plant extracts on P. maculata showed that there was a linear relationship between the concentrations of the individual extracts and the mortality of snails (Figure 1). This observation was in agreement with the findings of Chauhan and Singh [36] and EI-Din et al [37] wherein increases in the concentration of plant extracts resulted in high mortality rates of various pest snails. A similar positive correlation between the concentration of plant extracts (Sandoricum vidalii, Harpulia arborea, and Parkia sp.)…”
Section: Molluscicidal Activity Of Six Individual Plant Extractssupporting
confidence: 93%
See 4 more Smart Citations
“…An analysis of the molluscicidal activities of the six plant extracts on P. maculata showed that there was a linear relationship between the concentrations of the individual extracts and the mortality of snails (Figure 1). This observation was in agreement with the findings of Chauhan and Singh [36] and EI-Din et al [37] wherein increases in the concentration of plant extracts resulted in high mortality rates of various pest snails. A similar positive correlation between the concentration of plant extracts (Sandoricum vidalii, Harpulia arborea, and Parkia sp.)…”
Section: Molluscicidal Activity Of Six Individual Plant Extractssupporting
confidence: 93%
“…In the present study, the LC50 The result of the probit analysis on the mortality data of individual plant extracts on snails at LC50 and LC90 and fiducial limits are summarized in Table 4. Chi-square tests for probit analysis of This observation was in agreement with the findings of Chauhan and Singh [36] and EI-Din et al [37] wherein increases in the concentration of plant extracts resulted in high mortality rates of various pest snails. A similar positive correlation between the concentration of plant extracts (Sandoricum vidalii, Harpulia arborea, and Parkia sp.)…”
Section: Molluscicidal Activity Of Six Individual Plant Extractssupporting
confidence: 90%
See 3 more Smart Citations